1997
DOI: 10.1523/jneurosci.17-16-06152.1997
|View full text |Cite
|
Sign up to set email alerts
|

N-Type Calcium Channels in the Developing Rat Hippocampus: Subunit, Complex, and Regional Expression

Abstract: The expression of multiple classes of voltage-dependent calcium channels (VDCCs) allows neurons to tailor calcium signaling to functionally discrete cellular regions. In the developing hippocampus a central issue is whether the expression of VDCC subtypes plays a role in key phases such as migration and synaptogenesis. Using radioligand binding and immunoblotting, we show that some N-type VDCCs exist before birth, consistent with a role in migration; however, most N-VDCC subunit expression is postnatal, coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 80 publications
(158 reference statements)
3
35
0
Order By: Relevance
“…Indeed, activation of PKA was shown to antagonize ethanol modulation of N-and P/Q-type VGCCs in PC12 cells (Solem et al, 1997). N-type channel subunit composition modifications during development could be an additional explanation for the different sensitivity to ethanol throughout maturation (Jones et al, 1997;Vance et al, 1998;Lin et al, 1999;Pan and Lipscombe, 2000) Our findings are consistent with several reports indicating that these channels are important targets of ethanol. Through their modulation, ethanol inhibits dopamine release from rat striatal synaptosomes (Woodward et al, 1990), vasopressin release from rat neurohypophysial nerve terminals (Wang et al, 1991), and depolarization-induced rises in [Ca 2ϩ ] i in PC12 cells (Solem et al, 1997).…”
Section: Ethanol Affects Glutamatergic Synaptic Currents In Neonatal supporting
confidence: 92%
“…Indeed, activation of PKA was shown to antagonize ethanol modulation of N-and P/Q-type VGCCs in PC12 cells (Solem et al, 1997). N-type channel subunit composition modifications during development could be an additional explanation for the different sensitivity to ethanol throughout maturation (Jones et al, 1997;Vance et al, 1998;Lin et al, 1999;Pan and Lipscombe, 2000) Our findings are consistent with several reports indicating that these channels are important targets of ethanol. Through their modulation, ethanol inhibits dopamine release from rat striatal synaptosomes (Woodward et al, 1990), vasopressin release from rat neurohypophysial nerve terminals (Wang et al, 1991), and depolarization-induced rises in [Ca 2ϩ ] i in PC12 cells (Solem et al, 1997).…”
Section: Ethanol Affects Glutamatergic Synaptic Currents In Neonatal supporting
confidence: 92%
“…Previously, correlations in the localization and density of ␣ 1 and ␤ isoform mRNA in adult, embryonic, and postnatal rat brain predicted likely ␣ 1 /␤ complexes (48), but there were no conclusions reached in the case of the ␣ 1B/␤ complex. Another study concluded that there was no evidence for subunit switching in developing hippocampus as they targeted only the ␣ 1B /␤3 heteromultimers for analysis (59). In this study we have identified clear developmental trends in ␣ 1B /␤ composition from a population predominant in ␣ 1B ϩ ␤1b complexes (P2) to a population comprised of ␣ 1B ϩ ␤3 and ␣ 1B ϩ ␤4 complexes in mature rat brain.…”
Section: Figmentioning
confidence: 59%
“…Protein samples were prepared, electrophoresed, and transferred to nitrocellulose as described previously (26). The nitrocellulose membranes were incubated overnight at 4°C with the Kv4.2 polyclonal antibody at 1:1000.…”
Section: Methodsmentioning
confidence: 99%